Back‐projection stacking of P‐ and S‐waves to determine location and focal mechanism of microseismic events recorded by a surface array. (20th December 2015) - Vlček, J.; Fischer, T.; Vilhelm, J.
ABSTRACT: We present an automatic method of processing microseismic data acquired at the surface by a star‐like array. The back‐projection approach allows successive determination of the hypocenter position of each event and of its focal mechanisms. One‐component vertical geophone groups and three‐component accelerometers are employed to monitor both P‐ and S‐waves. Hypocenter coordinates are determined in a grid by back‐projection stacking of the short‐time‐average‐to‐long‐time‐average ratio of absolute amplitudes at vertical components and polarization norm derived from horizontal components of the P‐ and S‐waves, respectively. To make the location process more efficient, calculation is started with a coarse grid and zoomed to the optimum hypocenter using an oct‐tree algorithm. The focal mechanism is then determined by stacking the vertical component seismograms corrected for the theoretical P‐wave polarity of the focal mechanism. The mechanism is resolved in the coordinate space of strike, dip, and rake angles. The method is tested on 34 selected events of a dataset of hydraulic fracture monitoring of a shale gas play in North America. It was found that, by including S‐waves, the vertical accuracy of locations improved by a factor of two and is equal to approximately the horizontal location error. A twofold enhancement of horizontal location accuracy is achieved if a denser array of geophone groups is used instead of the sparse array of three‐component seismometers. The determined focal mechanisms are similar to those obtained by other methods applied to the same dataset.